Evaluation of the effect of biofertilizer application on primary production in pennisetum grasses (purple king grass and iniap 811), at 3 harvesting ages (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The present research was carried out to evaluate the effect of the addition of two levels of biofertilizer on the production of two cut grasses INIAP-811 and King Grass Morado, at 30 - 45 and 60 days of age. The three treatments were distributed in a randomized block experimental design and the variables were plant height, leaf/stem ratio, biomass production and nutritional quality. The results obtained for plant height were for King Grass at T3 with 243.2 cm, and for INIAP-811 at T2 with 193.13 cm, both at 60 days of age. In the protein variable, 16.88% was obtained at 30 days for T2 of the Purple King Grass, with INIAP-811 grass, the T3 treatment with 16.31% at 30 days of age. In the variable biomass production at 60 days of age, with 47.40 kg/m2 , the T2 for King Grass Morado, for INIAP-811, about 31.50 kg/m2 also at 60 days. In the leaf-to-stem ratio, T3 obtained 3.1:1 for King Grass Morado, while INIAP-811 obtained 2.05:1, both at 30 days of age. Based on the results obtained, we conclude that harvests at 45 and 60 days of age, plus the application of a biofertilizer significantly influences the agronomic and nutritional characteristics of the grass.